Rahmad Mega gave his blessings to son’s interest in Engineering - UMP, PNC (2018)
Suhazri Amrin Rahmad, 23, is the son of a 90’s popular rock singer in the country Rahmad Tohak or better known as Rahmad Mega, who preferred electrical engineering to singing.